The Profile Of Student-Aggressive Behaviors Reviewed From Gender-Role Identity: A Preliminary Study - Setyoningsih, Yunita Dwi; Hidayah, Nur; Atmoko, Adi; Radjah, Carolina L. (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to describe the aggressive behaviors of Junior High School (JHS) students in Semarang, Central Java, Indonesia. The applied-data analysis technique is quantitative descriptive with the discussed-percentage technique through the result review of each respondent item. The data collection methods are done through the Aggressive Behavior Scale (ABS) and counselor interview. From the ABS, it was found that generally, all aggressive behaviors of the JHS students in Semarang were categorized high with 4% or 7 of 164 respondents, moderate with 72% or 118 of 164 respondents, and low with 24% or 39 of 164 respondents. It was also found both aggressive behaviors on male and female students. The realizations of the aggressive behaviors were mostly dominated by verbal aggressiveness with 28.31%. Furthermore, through counselor interviews, it was found aggressive-behavioral condition triggered by mocking each other. It was a realization of verbal aggressiveness, which led to physical aggressiveness. Such student-aggressive behavior emergence was due to a lack of personal-emotion control by uttering inappropriate speech that, unfortunately, was considered typical and fine to express. This condition was due to students’ peers. This research recommends the necessity of counseling services to reduce student-aggressive behaviors.